Does organ and muscle plasticity vary by habitat or age in wintering Lesser Snow Geese Anser caerulescens caerulescens? - Jónsson, Jón Einar; Afton, Alan D. (Wildfowl, 2017)
Plasticity in organ and muscle size and function allows individuals to respond to changes in food quality or foraging behaviour, in accordance with cost-benefit hypotheses. Lesser Snow Geese Anser caerulescens caerulescens (hereafter Snow Geese) winter in rice-prairie and coastal-marsh habitats in southwest Louisiana, where the time that the birds spend foraging and walking, their composite diets, and associated fibre and energy contents, differ between these two habitats. We therefore hypothesised that: 1) Snow Geese that feed primarily in coastal marshes during winter would have larger digestive organs than those in rice-prairies, to adapt to the higher fibre content of their marsh vegetation diet; and 2) that leg muscles of Snow Geese feeding in rice-prairies would undergo greater hypertrophy and thus be larger than those in coastal marshes, because individuals in rice-prairie habitat spend more time walking while foraging. The first hypothesis applied to adults and juveniles alike, whereas under the second hypothesis, we knew from concurrent studies that juveniles walk more than adults and therefore predicted that they would have relatively larger leg muscles, after adjusting for body size. Seventy juvenile and 40 adult Snow Geese were dissected to test these two hypotheses about plasticity and hypertrophy with respect to habitat and foraging behaviour. Caeca and gizzard lengths were found to be larger for Snow Geese feeding in coastal marshes, where the food ingested is relatively high in fibre compared with the birds’ diet in the rice-prairies. Conversely, leg muscles were larger for Snow Geese foraging in rice-prairies, where the juvenile geese spend relatively more time walking. Although not fully grown, juvenile Snow Geese also varied in the length of their digestive system and hypertrophy in muscles in relation to habitat, reinforcing the view that the birds’ morphology adapts to different feeding habitats and diets.